Conservative-Progressive Power Games, Mutual Jostling in Africa and Resilience of Sino-African Relations under COVID-19 Wind - (:unkn) unknown (My University, 2021)
By taking the subprime crisis as its historical fact of analysis and game theory as its theoretical explanatory basis, this paper aims to explain and demonstrate why Sino-African relations may well withstand in the ongoing "conservative-progressive power games" in Africa under COVID-19 wind, even though they are being further jostled by the "conservative's offensive". To support my central point, I start from the assumption that, as was just the case with the subprime crisis, the socioeconomic and financial dimension will once again become a compass [but also a barometer] in the decisions and actions of all the states at stake-the "conservatives", the "progressives", as well as the different African countries. Thus, the improvement of the socioeconomic and financial situation on its own territory will become the major challenge of almost all these states at stake. And China, which is less affected by the socioeconomic and financial crisis caused by COVID-19 than the "conservatives", will be well able to bear the costs of its increasing engagement on the African continent. Although a relative decline or quasi-stagnation of its engagement on the continent can be noted-but rather less than in the case of the "conservatives", due of course to the comparative shocks of this crisis caused by COVID-19 on their economic activities. In this same logic, another explanatory point is that, if Sino-African relations fall, a big hole will be left in African economies-because of China's pronounced economic integration in Africa. A hole that the "conservatives"-hit hard by this crisis due to COVID-19, will not be able to fill during this critical moment, in the sense of satisfying the demands of Africa-which is also hit hard by the same crisis. Finally, the game theory as an explanatory theoretical basis, via the five (5) points game, imagined in terms of gain on the African continent, according to the costs of "conservative-progressive engagements"-which are conditio
Keywords: African Research